A Flipped Classroom to Enhance Students’ Self-Direction in Informatics and Physics Engineering - Dina Adinda (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
As one of the blended learning forms, a flipped classroom has its specific typology to differentiate itself from other blended learning models. Aims to support student-centered learning activities in which self-direction in learning might be fostered, the effect of flipped classroom scenario to students' self-direction had never been reviewed. This work, performed at the University of Strasbourg, involved lecturers who teach informatics and physics engineering course. First, observations of the online learning environments and face-to-face classes had been managed. Second, a pre and post-test questionnaire, which aimed to measure its participants' progress on self-direction, had been fulfilled by the students. This study pointed out that students enrolled in a translated flipped classroom course had not developed their self-direction competence. However, the significant progress of students' self-direction in learning has been documented among students enrolled in a course with an interactive flipped classroom scenario.